Crystal structure of N-carbamothioyl-2- methylbenzamide - Adam, Farook; Ameram, Nadiah; Wai, Mun Tan (International Union of Crystallography, 2015)
There are two molecules in the asymmetric unit of the title compound, C9H10N2OS. In one, the dihedral angle between the aromatic ring and the carbamothioyl group is 52.31 (7) and in the other it is 36.16 (6). Each molecule features an intramolecular N—H O hydrogen bond, which generates an S(6) ring and the O and S atoms have an anti disposition. In the crystal, molecules are linked by N—H S and N—H O hydrogen bonds, generating separate [130] and [130] infinite chains. Weak C—H O and C—H S interactions are also observed.